Avaliação do potencial anti-inflamatório do soro de leite caprino na colite experimental e na resposta celular - Araújo, Daline Fernandes de Souza (2016)
Inflammatory Bowel Disease (IBD) is characterized as an uncontrolled chronic inflammation of the intestinal mucosa and mainly includes two pathologies: Crohn's disease and ulcerative colitis. Accordingly, the local immune system remains compromised and the intestine intensely inflamed, due to an inability of decreasing inflammatory responses. Complementary and alternative medicines have been of great interest for the treatment of IBD, with the aim to improve the side effects of commonly used drugs. Goat whey present oligosaccharides and conjugated linoleic acid with different functional properties, but also an effect on intestinal incipient modulation. This thesis was divided into two studies: the first being goat whey ability in preventing intestinal inflammation in an inflammation model induced by acetic acid in rats, evaluated by comparing it with a standard sulfasalazine medicine used in the treatment of DII; in the second study, the anti-inflammatory effect of the whey colitis model induced by 2,4-dinitrobenzenesulfonic acid in mice. In the first, the pre-treatment with goat whey (1, 2 and 4 g. Kg-1) and sulfasalazine (250 mg. Kg-1) improved the inflammatory markers (myeloperoxidase, leukotriene B4 and pro-inflammatory cytokines) and oxidative stress (total content of glutathione and malondialdehyde) in colonic tissue of rats. Histological and immunohistochemical evaluation of colonic tissue showed cytoarchitecture preservation and reduction in COX-2 expression, respectively, as well as iNOS and MMP-9 in conjunction with an increase in SOCs-1 expression. The results suggest that goat whey exerted a preventive effect against intestinal damage induced by acetic acid, showing similar efficacy to sulfasalazine, and thus is a potential treatment for human inflammatory bowel disease. In the second model, we used the best dose of the first to conduct different analyses. In the second model with a different inducing agent of IBD was used to dose goat whey that Showed better results in improving of intestinal inflammation the previous study. This study, there was also an improvement of intestinal damage in the group of animals, confirmed by evaluating colonic inflammation and colonic gene expression of pro-inflammatory markers IL-6, IL-1β, IL-17,TNF-α, iNOS, ICAM- 1, MMP-9, regulators of intestinal epithelial integrity (MUC-2, MUC-3, occludin and ZO-1) and supressor of cytokine signaling (SOCS-1). The anti-inflammatory properties of the goat whey were demonstrated by an in vitro study on murine macrofhages line Raw 264 and CMT-93 cells derived from murine rectum carcinoma which promoted a significant reduction in nitric oxide production and IL-6. Thus, goat whey shown as an innovative product in the prevention and control of intestinal inflammation in murine models.